Language, Culture and Marginal Identity in Post-1971 Bengali Fiction on Fishing Communities (London Journal of Research In Humanities and Social Sciences, 2026)
This study explores the interrelationship between language, culture, and identity through a cultural-linguistic analysis of marginalised fishing communities as represented in post-1971 Bāṁlā (Bengali) fiction from Bangladesh and West Bengal. Situated at the intersection of cultural studies and sociolinguistics, the study conceptualises language not merely as a medium of representation but as a constitutive social practice through which cultural meanings, power relations, and collective identities are produced and negotiated.Drawing on theoretical perspectives from linguistic anthropology, discourse analysis, and cultural theory, the essay treats culture as a dynamic and contested repertoire of meanings rather than a fixed system, and identity as plural, relational, and historically situated. Within this framework, language emerges as both a symbolic resource and a political marker-capable of sustaining cultural memory while simultaneously reflecting structures of exclusion. The analysis distinguishes between cultural identity, rooted in shared livelihood practices and linguistic forms, and ethnic identity, shaped by political categorisation and access to resources in complex societies.The core analysis examines selected post-Liberation Bāṁlā novels that depict fishing communities (variously known as jele, kaivarta, mālo, jaladāsa), focusing on vernacular speech, occupational registers, and dialogic exchanges. These literary discourses reveal how fishermen’s language encodes marginalisation through caste, class, and occupational stigma, while also functioning as a site of resistance, resilience, and self-assertion. Particular attention is paid to moments where marginal speakers appropriate linguistic agency to challenge dominant social norms, as well as to gendered voices that articulate survival and cultural continuity.The article argues that linguistic difference is not merely an index of social hierarchy but a critical force in sustaining cultural identities and alternative worldviews. By foregrounding marginalised speech communities in Bāṁlā literature, the study contributes to cultural studies and sociolinguistics by demonstrating how language mediates power, belonging, and resistance within postcolonial South Asian contexts.
Keywords: Bangla literature; cultural discourse; fishing communities; language and identity; marginalized communities; postcolonial studies; sociolinguistics